THE INFLUENCE OF CUSTOMER TRUST AND SATISFACTION ON TOKOPEDIA CUSTOMER LOYALTY - Ian Zulfikar (SEAN Institute, 2021)
The pace of progress in the world of business is accelerating. This is because of the growth of information and communication technology (ICT), which has made it simpler for people to engage in business dealings over the internet, often known as e-commerce. Tokopedia is among the most well-known applications for conducting business online. The purpose of this research is to investigate whether or not Tokopedia's commitment to its customers is influenced by factors such as trust and satisfaction among those customers. The members of the general public who live in Cimahi City and who have used and purchased products from Tokopedia made up this study's population, and 109 people participated as respondents in this research. The methodology utilized in this investigation is quantitative in nature and of the associative type. According to the findings, the variables of trust and customer satisfaction simultaneously and partially influenced Tokopedia's customer loyalty in Cimahi City, with a combined influence of 44.8% on customer loyalty due to the variables of trust and customer pleasure.